Submarine groundwater discharge and associated nutrient flux from southwest coast of India. (January 2021) - George, Mintu Elezebath; Akhil, T.; Remya, R.; Rafeeque, M.K.; Suresh Babu, D.S.
Abstract: The nutrient discharge associated with submarine groundwater discharge (SGD) into the Arabian Sea has been investigated for the first time using the Radon isotope ( 222 Rn) mass balance model at three sites along the southwest coast of India. The SGD flux varied in the range of 49.48×10 4 - 335.84×10 4  m 3 /day, with high (low) discharge during the low (high) tide. SGD delivers a considerable amount of the nutrient into the Arabian Sea with 2.10×10 4 to 11.66×10 4  mol/day dissolved inorganic nitrogen (DIN), 1.23×10 2 to 56.31×10 2  mol/day dissolved inorganic phosphate (DIP), and 7.28×10 4 to 24.44×10 4  mol/day dissolved silicate (DSi). This significant nutrient input to the coastal waters through SGD is mainly attributed to the land-use practices like agricultural activities, improper waste disposal, and thickly populated coastal settlement zones. The increase in the nutrient discharge may lead to phytoplankton bloom in the nearshore environment and can accelerate seasonal coastal hypoxia over the western Indian shelf. This evidence of considerably high nutrient flux through SGD advocates the importance of understanding SGD associated flux along the southwest coast of India to maintain a sustainable ecological balance. Highlights: The study investigated the nutrient flux through submarine groundwater discharge (SGD) to the the southwest coast of India. Considerably high nutrient discharge through SGD recorded, and groundwater discharge found to be fluctuating with the tide. Geology of the area, hydraulic gradient of water table, drainage and land use patterns define this seaward groundwater and nutrient transport.